The Role of Local Community Leaders in Electoral Mobilization: A Case Study of the 2024 Deli Serdang Regent Election - Maya Br Ginting; Prayetno (International Journal of Education and Humanities, 2025)
This study employed a narrative inquiry method. It used qualitative techniques such as in-depth. The lack of understanding and participation of the people of Pematang Johar village in the Regional Election contest is a big challenge for local community leaders in winning the candidate pair. Local community leaders use their positions, relationships, and social networks to attract the people's voices. This research aims to find out the role of local community leaders in attracting the voices of the people of Pematang Johar Village, Labuhan Deli District, Deli Serdang Regency, in the 2024 Deli Serdang Regent Election. The method used in this study is qualitative descriptive. The theories used in this study are John T. Sidel's theory of local bossism and Joel S. Migdal's theory of local strongman. The type of data used is primary data and secondary data. Data collection techniques are carried out through observation, interviews, and documents. Data analysis techniques are reduction, display, verification, and triangulation. The study results show that local community leaders actively participate as mobilizers, motivators, and facilitators in winning Asriludin Tambunan and Lom-lom Suwondo candidate pairs. Hermawan, as a youth leader and sub-district coordinator, plays his role in the electoral system by capturing many people's votes, assisted by other important figures such as businessmen, youth, and religious figures, in launching his role as social, economic, and political capital. Hermawan takes advantage of his position and spreads his network to various circles, ranging from millennials to political elites. Local community leaders use economic capital for campaign purposes. Local community leaders also play a role as socio-political control that becomes a locking and motivating force to support the candidates loyally